Characteristics of spatial and temporal variations in the free-fall process of a granular flow on an inclined surface - Guo Xiaohong; Wen Zhimei; Gao Lili (E3S Web of Conferences)
Based on the one-factor method (with different mass flow rates), experiments were carried out on the diffusion phenomenon of particle flow, diffusion diameter, transport velocity and dust concentration to derive the relationship between mass flow rate and each field quantity. The results show that: with the increase of mass flow rate, the particle flow diffusion phenomenon is more obvious under the influence of tangential friction and horizontal resistance, and is accompanied by the generation of vortex; the diffusion diameter, transport velocity and dust concentration all show a tendency to increase with the increase of mass flow rate, and the duration of the high concentration of dust at 0.152kg/s reaches 10s, and the dust transport velocity does not increase any more when the height of the downward drop is increased to 0.33m. When the drop height increased to 0.33m, the dust transport velocity no longer increased.